Step frequency and step length of 200-m sprint in able-bodied and amputee sprinters - Hobara, H.; Sano, Y.; Kobayashi, Y.; Heldoorn, T. A.; Mochimaru, M. (International Journal of Sports Medicine, 2016)
The goal of this study was to examine the hypothesis that the difference in the 200-m sprint performance of amputee and able-bodied sprinters is due to a shorter step length rather than a lower step frequency. Men`s elite-level 200-m races with a total of 16 able-bodied, 13 unilateral transtibial, 5 bilateral transtibial, and 16 unilateral transfemoral amputee sprinters were analyzed from publicly available internet broadcasts. For each run, the average forward velocity, step frequency, and step length over the entire 200-m distance were analyzed for each sprinter. The average forward velocity of able-bodied sprinters was faster than that of the other 3 groups, but there was no significant difference in average step frequency between able-bodied and transtibial amputee sprinters. However, the average step length of able-bodied sprinters was significantly longer than that of the transtibial amputee sprinters. In contrast, the step frequency and step length of transfemoral amputees were significantly lower and shorter than those of the other 3 groups. These results suggest that the differences in 200-m sprint performance between able-bodied and amputee sprinters are dependent on amputation level.